In Memoriam Fátima Cáceres de Baldarrago (1960-2020) - Arana, César (2021)
Fátima Cáceres de Baldarrago was a Peruvian botanist recognized for her knowledge of the Cactaceae family and the flora of southern Peru. She had an active interest in the different aspects of "Scientia amabilis". Thus, her concern to learn from scientific collections, and the management and review of various taxa led her to do internships at the Instituto Nacional de Innovación Agraria, La Joya, Arequipa, and at the Herbarium Truxillense of the Universidad Nacional de Trujillo, La Libertad, as well as in the Museo de Historia Natural de la Universidad Nacional Mayor de San Marcos, which she created a permanent collaborative connection.